A Promise of the Future or A Dead End: Occupation and Social Conflict in Palm Oil Plantations in West Pasaman - Indrizal, Edi; Nurti, Yevita; Ermayanti, Ermayanti; Irwandi, Ade (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
This paper discusses the conflict that occurred on land owned by PT. PHP I, which was occupied by the Nagari Kapa community as their customary land. The community requested land rights in order to gain access to the land based on the Babingkah Adat customary system. Therefore, this paper analyses the nature of customary provisions in land ownership and the community's actual motives for occupying PT. PHP I's land. Using critical ethnography approach, it analyses social relations, social inequality, and capitalist hegemony in the palm oil industry. Data was collected using participatory observation, in-depth interviews, and text analysis of the perspectives of the community, traditional leaders, and the legality of land use. The study shows that the transfer of land by traditional leaders (ninik mamak) Nagari Kapa to the state (West Pasaman government) in 1997 was a statement that contained political, legal, and customary elements. Therefore, the customary framework cannot be accessed and cannot be fully applied. The customary framework cannot be accessed and cannot be fully applied. The occupation of land by the Nagari Kapa community represents their resistance and resilience to defend their land. They are not only fighting and reclaiming the land taken by PT. PHP I, but also opposing the arbitrary actions of their ninik mamak, who unilaterally handed over the land to another party. Thus, the social awareness of occupying PHP I's land is a form of aspiration and resistance by the community to reclaim their land rights..